A Simplified Theory of Electroadhesion for Rough Interfaces - Ciavarella, Michele; Papangelo, Antonio (Frontiers in Mechanical Engineering, 2020)
Electroadhesion is a very hot topic in tribology due to its implications in the science of surface haptics. Building on theories of Persson, we derive a simpler theory for electroadhesion between rough surfaces using BAM (Bearing Area Model) of Ciavarella. The theory is derived for both cases of conducting and insulating bodies and shows that pull-off forces depend mostly on the applied voltage, on the surface height rms and on the longest wavelength in the surface representation. However, real contact area and friction additionally depend on rms slopes and hence on truncation of the roughness spectrum. Two stickiness criteria have been derived based on the present theory and on the energy balance proposed by Persson and Tosatti. The coefficient of friction decays with normal pressure tending to a plateau in a manner which is consistent with existing experiments.